Bermain Seru, Belajar Maksimal: Penerapan Play-Based Learning untuk Anak ADHD [Fun Play, Maximum Learning: Implementation of Play-Based Learning for ADHD Children] - Alexander, Pieter; Devi Tiar Mauli; Yanie Pattiasina (Magister Teknologi Pendidikan Fakultas Ilmu Pendidikan, Universitas Pelita Harapan, 2025)
The study seeks to understand how enjoyable and meaningful learning can be applied to address the learning difficulties faced by children with ADHD. ADHD, or attention deficit hyperactivity disorder, is a neurodevelopmental disorder characterized by difficulty concentrating, impulsivity, and hyperactivity, which can significantly affect academic performance. Play-based learning is a promising pedagogical approach that can be adapted for children with ADHD. By engaging in playful activities, educators can introduce and guide meaningful learning experiences. This research aims to understand the implementation of play-based learning for children with ADHD. This qualitative descriptive study employed a literature review to explore existing research on this topic. The findings suggest that play-based learning can be beneficial for children with ADHD, contributing to improved focus, increased motivation, and enhanced social interaction skills. This is because play-based learning integrates seamlessly with other aspects of child development, creating a fun and meaningful educational experience that promotes efficient and effective teaching and learning.